Luis Martin, The intellectual conquest of Peru — The Jesuit College of San Pablo, 1568-1767 (New York, Fordham University Press, 1968), XII y 194 pp. - Denegri Luna, Félix (Revista Histórica, 2025)
Sin resumen.